2022
DOI: 10.1007/s00109-022-02250-y
|View full text |Cite
|
Sign up to set email alerts
|

Stress induces major depressive disorder by a neutral sphingomyelinase 2-mediated accumulation of ceramide-enriched exosomes in the blood plasma

Abstract: Major depressive disorder (MDD) is a very common, severe disease with a lifetime prevalence of ~ 10%. The pathogenesis of MDD is unknown and, unfortunately, therapy is often insufficient. We have previously reported that ceramide levels are increased in the blood plasma of patients with MDD and in mice with experimental MDD. Here, we demonstrate that ceramide-enriched exosomes in the blood plasma are increased in mice with stress-induced MDD. Genetic studies reveal that neutral sphingomyelinase 2 is required f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…It was shown previously that Cer negatively affected PLD activity [ 53 ]. In line with this, NSM2-generated Cer impaired PLD activity in mice models of major depressive disorder [ 8 ]. Published data on smpd3 −/− chondrocytes showed transcriptional upregulation of Golgi-associated SMS1 thereby affecting the NSM2-SMS1 cycle in the Golgi apparatus and DAG homeostasis [ 30 ].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…It was shown previously that Cer negatively affected PLD activity [ 53 ]. In line with this, NSM2-generated Cer impaired PLD activity in mice models of major depressive disorder [ 8 ]. Published data on smpd3 −/− chondrocytes showed transcriptional upregulation of Golgi-associated SMS1 thereby affecting the NSM2-SMS1 cycle in the Golgi apparatus and DAG homeostasis [ 30 ].…”
Section: Discussionmentioning
confidence: 79%
“…Its usage of sphingomyelin (SM) as a substrate for the production of Cer at neutral pH was demonstrated more than a decade ago [ 7 ]. NSM2 mediates stress and inflammation induced Cer generation [ 8 , 9 , 10 ]. It is implicated in bone mineralization, growth arrest, apoptosis, and inflammation [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ceramides were analyzed in detail per targeted and untargeted lipidomic analyses because previous studies have shown that ceramides in plasma are increased in mental disease [8,80], particularly major depression [81]. In mice, depression-like behavior occurs upon exposure to chronic unpredictable mils stress (CMUS) [82,83], which is one of the popular depression models and is associated with changes of ceramide metabolism via acidic sphingomyelinase which is believed to be triggered by stress [84] and may lead to depression [85]. The results of targeted and untargeted ceramide analyses were highly consistent (Figure 6 middle), but contrary to expectations, ceramides were not associated with perceived stress.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its up to 20-fold higher expression in the brain compared to peripheral tissues [18], this enzyme could be of increased interest for neuroscience. Indeed, NSM-2 has been involved in the biogenesis of exosomes and the release of extracellular vesicles with relevance to many conditions, from cardiovascular [19] and cardiometabolic [20] diseases [19] to anxiety [21], major depressive disorder [22], and alcohol addiction [23,24]. While different tissue types are easily available from animal models, including brain regions, biological material from patients is mostly limited to peripheral liquid biopsies such as easily available blood, saliva, or urine samples, whereas tissue biopsies require more invasive procedures and may pose ethical problems.…”
Section: Introductionmentioning
confidence: 99%